COVID-19 and the Local Tradition of the People of North Maluku - Susanto Zuhdi; Irfan Ahmad; Andi Sumar Karman; Safrudin Abdulrahman; Noor Fatia Lastika Sari (Journal of Maritime Studies and National Integration, 2022)
Dealing with pandemics has never been a new issue, seen from the perspective of the history of mankind. It was a manifestation of l’histoire se répète. As an example, a few centuries prior to the Black Death and Cholera Outbreak, Galvao wrote that a respiratory disease had broken out in Ternate around 1553, while De Clercq mentioned a deadly plague in Bacan throughout 1706-1709. Traditionally, these issues were treated as a result of badly conducted supernatural rituals. They opted for herbal treatments, and exorcism, and even migrated to the hinterland as an act of self-quarantine. Today, COVID-19 has become a global pandemic and reached the islands of North Maluku province, with Ternate as the epicentrum of the outbreak. However, there has been a resolution, which facilitates another traditionally crafted effort, such as Liliyan, Barifola, and Rera, based on the oral tradition mentioned in Dora Bololo. We seek to discover how far cultural aspect would affect the economic and social life of the locals, as well as in what domain tradition and local practice should contribute to the current situation. Thus, this research aims to understand and analyze such a combination of traditionally generated solutions within a current scientific framework, especially on how history, anthropology, as well as archival, and memory study could understand the living aspect of the locals and therefore apply Vansina’s (1985) approach in oral tradition as historical sources.